Liquid Crystal Optical Device - Bennis, Noureddine (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Special Issue "Liquid Crystal Optical Devices" discusses recent developments in the rapidly advancing subject of liquid crystals (LCs).